Metabolic syndrome in patients with major depressive disorder: A study of one year incidence and associated factors - Charnsil, Chawanun; Pilakanta, Sutrak (Biomedical Sciences and Clinical Medicine, 2018)
Objective To examine the one year incidence of metabolic syndrome and factors associated with major depressive disorder. Methods Patients who had came for treatment of major depressive disorder (MDD) at Maharaj Nakorn Chiang Mai Hospital were screened using the metabolic syndrome criteria proposed by the American Heart Association/National Heart, Lung, and Blood Institute (updated ATPIII). Subjects who did not meet the criteria of metabolic syndrome were screened again at a one year follow-up. Age, history of atypical antipsychotic medication usage, duration of illness, severity of illness, and family history of metabolic syndrome were assessed as factors potentially associated with the metabolic syndrome. Data was analyzed using, standard deviation, student t-test, chi-square test, and Fisher’s exact test and is presented as percentages and means. Results One hundred and forty subjects were recruited of whom 53 were excluded because they already had metabolic syndrome. After one year, 77 of the 87 returned for a follow-up visit and were again screened for metabolic syndrome. The one-year incidence of metabolic syndrome, evaluated according to ATP III criteria, was 16.9% (13 subjects). Both Baseline triglyceride and HDL levels were significantly associated with metabolic syndrome in patients with major depressive disorder (p ≤0.001). Age, history of atypical antipsychotic medication usage, duration of illness, severity of illness, and family history of metabolic disorders were not found to be associated with metabolic syndrome. Conclusions MDD patients are likely to have or to develop metabolic syndrome. These findings emphasize the importance of assessing and monitoring metabolic syndrome in MDD patients, especially patients who have both high triglyceride and HDL levels.